The Principle of Presumption of Innocence and Overcriminalization: A Critical Study of The Influence of Social Media in The Digital Era (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This study aims to examine the influence of social media on the presumption of innocence and the phenomenon of overcriminalization in the digital era. The presumption of innocence is a fundamental legal principle, which states that every individual is not considered guilty until proven otherwise. However, with the rapid development of social media, information is often disseminated without adequate verification, resulting in stigma and negative judgments against individuals who are considered to have committed crimes. The phenomenon of overcriminalization refers to the tendency to consider certain actions as crimes, which is often triggered by public opinion formed through narratives on social media. Social media, with its ability to spread information quickly and widely, often creates virality that can change public perception in an instant. News or accusations that were initially obtained from non-credible sources can quickly become trends, triggering emotional reactions and excessive responses from the public. This study uses a qualitative approach by analyzing various case studies and related literature to explore the relationship between social media dynamics, public perception, and its impact on legal principles. The results show that social media can undermine the presumption of innocence by creating public pressure that encourages repressive actions before the legal process takes place. In addition, excessive criminalization often occurs as a response to inaccurate information and sensationalism that develops on social media platforms. The conclusion of this study emphasizes the need for stricter regulation of the dissemination of information on social media and the importance of educating the public about respecting the principle of the presumption of innocence. This aims to maintain justice and human rights in an increasingly complex digital era.